Study of intense electron beams produced by high voltage pulsed glow discharges - Rocca, Jorge J., author; Murray, C., author; Szapiro, B. T., author; Reesor, N., author; Ranea-Sandoval, H. F., author; IEEE, publisher (Colorado State University. Libraries, 1987)
We report the generation of high-current-density (20A/cm2) pulsed electron beams from high-voltage (48-100 kV) glow discharges using cathodes 7.5 cm in diameter. The pulse duration was determined by the energy of the pulse generator and varied between 0.2 μs and several microseconds, depending on the discharge current. The largest electron beam current (900 A) was obtained with an oxidized aluminum cathode in a helium-oxygen atmosphere. An oxidized magnesium cathode produced similar results, and a molybdenum cathode operated at considerably lower currents. A small-diameter (< 1 mm) well-collimated beam of energetic electrons of very high current density (> 1 kA/cm2) was also observed to develop in the center of the discharge. Electrostatic probe measurements show that the negative glow plasma density and the electron beam current have a similar spatial distribution. Electron temperatures of 1-1.5 eV were measured at 7 cm from the cathode. The plasma density (8.5 • 1011cm-3 at 450 A) was found to depend linearly on the discharge current. In discharges at high currents a denser and higher temperature plasma region was observed to develop at approximately 20 cm from the cathode. We have modeled the process of electron beam generation and predicted the energy distribution of the electron beam. More than 95 percent of the electron beam energy is calculated to be within 10 percent of that corresponding to the discharge voltage.